Intestinal nematodes Ascaris lumbricoides Eggs on Fruits in Jakabaring Central Market Palembang City - Febriana Ayu Shavira; Dalilah Dalilah; Susilawati Susilawati; Gita Dwi Prasasty; Chairil Anwar (Fakultas Kedokteran Universitas Sriwijaya, 2021)
Soil-Transmitted Helminths (STH) intestinal nematodes hich is still a health problem in Indonesia. This disease could occur due to various factors, such as the habit of not washing the fruit before consumption. Consumption of fruits helps meet nutritional needs to protect the body from various diseases. This research aimed to determine whether there is STH egg contamination in fruits sold at the Jakabaring Central Market. This research was a descriptive-observational study. The fruit sample were collected from Jakabaring Central Market. A total of 50 fruits samples in this study consisted of Citrus sinensis, Cucumis melo, Ananas Comosus, Musa sp., and Citrullus lanatus The sample processing was carried out using the sedimentation method. About 200 grams of fruit skin samples were immersed in 0.2% NaOH. Microscopic observations were made at the Biooptic Laboratory and Medical Chemistry Laboratory of FK Universitas Sriwjaya. A total of 9 (18%) samples were showed positive results of STH contamination, which were 7 samples of pineapple Ananas comosus (14%) and 2 samples of watermelon Citrullus lanatus (4%). From the 9 positive samples, 35 Ascaris lumbricoides infertile-decorticated eggs were found. Thus, contamination of Ascaris lumbricoides eggs in fruits were detected and its non infective stage Jakabaring Central Market Palembang City. Although all eggs found in non infective stage , with sufficient percentage of contamination, improving hygiene before consuming must be considered.